2008
DOI: 10.1149/1.2795841
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV Irradiation on Threshold Voltage and Subthreshold Slope in Pentacene TFT

Abstract: We report the influence of UV irradiation on the electrical properties of pentacene thin-film transistors ͑TFTs͒ with SiO 2 gate insulator. The threshold voltage ͑V th ͒ shifted from −9.0 to −5.1 V and subthreshold slope reduced from 3.6 to 1.1 V/dec by the treatment before pentacene deposition. The UV treatment reduced the surface energy by removing the hydroxyl groups at the SiO 2 surface. Thus, molecular packing of pentacene on the UV-treated SiO 2 was improved, lowering the ͉V th ͉ value via the reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(23 reference statements)
1
1
0
Order By: Relevance
“…On the basis of this study, it is definitely found that hydroxyl groups act as charge carrier trapping sites. Considering some previous works about the interfacial trap density on various dielectric layers such as SiO 2 , and self‐assembled monolayer deposited on SiO 2 , and Al 2 O 3 , our calculated interfacial trap density is in a reasonable range . Compared with the hydroxyl group‐existing polymeric buffer layer, it is found that the hydroxyl group‐free polymeric buffer layer is much more efficient in minimizing the N trap .…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…On the basis of this study, it is definitely found that hydroxyl groups act as charge carrier trapping sites. Considering some previous works about the interfacial trap density on various dielectric layers such as SiO 2 , and self‐assembled monolayer deposited on SiO 2 , and Al 2 O 3 , our calculated interfacial trap density is in a reasonable range . Compared with the hydroxyl group‐existing polymeric buffer layer, it is found that the hydroxyl group‐free polymeric buffer layer is much more efficient in minimizing the N trap .…”
Section: Resultssupporting
confidence: 53%
“…Considering that the magnitude of SS represents the quality about how soon the OFETs turn from off state to on state, a lower value is desirable for fast switching. The SS is determined from the following equation in the subthreshold regime at the transfer characteristic curves: SS=VitalicG(logIitalicD)…”
Section: Resultsmentioning
confidence: 99%